EATING EPILEPSY - I. G. Rudakova; K. Yu. Mukhin; M. B. Mironov; M. O. Abramov (Русский журнал детской неврологии)
Eating epilepsy (EE) is one of the types of reflex epilepsy. The authors give the definition, classification position, possible pathogenic mechanisms and etiological factors associated with EE, as well as the semiology of seizures, the data of neuroimaging and electroencephalography and approaches to patient management and drug treatment. They also describe their observation of an 11-month-old girl with symptomatic focal temporal lobe epilepsy with focal dialeptic seizures provoked by eating.